Comparing e-bike and conventional bicycle use patterns in a public bike share system: A case study of Richmond, VA - Yifan Yang; Elliott Sloate; Nashid Khadem; Celeste Chavis; Vanessa Frías-Martínez (Journal of Cycling and Micromobility Research)
Bicycle-sharing systems have emerged as a viable transportation alternative in numerous urban areas, owing to their multifaceted benefits. These benefits include reduced transportation expenses, health improvements, and decreased emission levels. While extensive research has been conducted on travel behaviors in shared bicycle systems, there is currently a lack of research on travel behaviors changes with the introduction of e-bikes. This study presents a comprehensive analysis of the similarities and differences between e-bike (pedelec) and conventional bicycle use in a bike share system in Richmond City, Virginia.The results show that pedelecs are generally associated with longer trip distances, shorter trip times, higher speeds, and lower rates of uphill elevation change. The origin–destination analysis considering the business, mixed use, residential, and other uses shows extremely similar trends, with a large number of trips staying within either business or residential locations or mixed use. The roadway use analysis shows that pedelecs are used farther outside of the city than bikes.